Prevalence of single-nucleotide variants in twenty-five pharmacogenes from a Cuban sample cohort - Reyes-Reyes, Elizabeth; Herrera-Isidrón, José Alfredo; Cuétara-Lugo, Elizabeth; Shkedy, Zhiv; Valkenborg, Dirk; Pérez-Novo, Claudina Angela; Fernández-Peña, Gisselle; González-Pérez, Idania; Fernández-Pérez, Miguel David; Vanden-Berghe, Wim; Rodeiro-Guerra, Idania (Frontiers in Pharmacology, 2024)
Cuban population is genetically diverse and information about prevalence of genetic variants is still limited. As complex admixture processes have occurred, we hypothesized that the frequency of pharmacogenetic variants as well as drug responses may vary within the country. The aims of the study were to describe the frequency distribution of forty-three single nucleotide variants (SNVs) from twenty-five genes of pharmacogenetic interest within Cuba population and in relation to other populations, while taking into consideration some descriptive variables as place of birth and skin color. Materials and Methods. SNV were analyzed in 357 unrelated healthy Cuban volunteers. Genotype and allele frequencies, as well as ancestry proportions were determined and pairwise fixation index (Fst) was evaluated. Results. Hardy-Weinberg equilibrium deviations in six loci (rs11572103, rs2740574, rs776746, rs3025039, rs861539, rs1762429) were identified. Minor allele frequencies ranged from 0.00 to 0.15 for variants in genes encoding xenobiotic metabolizing enzymes. They also ranged from 0.01 to 0.21 for variants in DNA repair, growth factors, methyltransferase, and methyl-binding proteins, while they were from 0.04 to 0.27 for variants in the O-6-Methylguanine-DNA Methyltransferase enzyme. Moderate genetic divergence was present upon comparison to Africans (Fst = 0.071, SD 0.079) and 19 markers exhibited moderate to large genetic differentiation. Average European, African, and Amerindian ancestry were 67.8%, 27.2% and 5.3%. Ancestry proportions differed by skin color and birthplace for the African and European components, exception was between individuals from Western and Eastern for the European component. Meanwhile, the statistical significance varied in comparisons by skin color and birthplace within the Amerindian component. Low genetic divergence across geographical regions was observed. We identified twelve variants with moderate to large differentiation in White versus Black individuals comparison. Conclusions. Altogether, our results may support national strategies for the introduction of pharmacogenetic tools in clinical practice as a form to develop precision medicine in Cuba.